TRAYECTORIAS, SABERES Y CONOCIMIENTOS LOCALES FRENTE A LAS DIFICULTADES DE IMPLEMENTACIÓN DE PROYECTOS SOCIALES - Macarena Perusset (Boletín Geográfico)
Nowadays we belong to a world subordinated to capital gain rationality, where concentration of scientific and technological capabilities is linked to concentration of earnings and profits. In that way, knowledge becomes an instrument of domination and supremacy. Latin America, especially our country, inside this frame turns into a generator of raw materials and take up a stance of dependency of central countries. Against this background, we propose in this paper the enormous potential that our countries have to develop science and technology for social inclusion primary for strategic sectors linked to land use and the use and conservation of natural resources and leveraging knowledge pondering and customs of local communities for employment opportunities.